Insidious. Chapter 3 [videorecording (Blu-Ray)] - Whannell, Leigh, 1977-; Whannell, Leigh, 1977-; Mulroney, Dermot; Scott, Stefanie, 1966-; Sampson, Angus (Sony Pictures Home Entertainment, 2015)
The new chapter in the terrifying horror series is a chilling prequel, set before the haunting of the Lambert family, reveals how gifted psychic Elise Rainier reluctantly agrees to use her ability to contact the dead in order to help a teenage girl who has been targeted by a dangerous supernatural entity.